The Vatly Radio Telescope: Performance Study - Phuong, Nguyen Thi; Diep, Pham Ngoc; Pierre, Darriulat; Nhung, Pham Tuyet; Anh, Pham Tuan; Dong, Pham Ngoc; Hoai, Do Thi; Thao, Nguyen Thi (Communications in Physics, 2014)
A detailed account of the performance of the VATLY radio telescope, operated in HaNoi on and near the 21 cm HI line, is given. Drift scans across the Sun are used to measure the dependence of the gain on frequency and power, revealing small nonlinearities at or below the percent level. Interferences associated with the electromagnetic pollution in the Ha Noi environment are described. The sensitivity of the instrument is discussed and demonstrated with the detection of the Crab. The reliability of the measurement of the spectral flux density is illustrated by comparing solar flux data measured in Ha Noi and at the Australian observatory of Learmonth